Project unlonely : healing our crisis of disconnection [book club bag] - Nobel, Jeremy (Avery, an imprint of Penguin Random House, 2023)
"Even before 2020, chronic loneliness was a private experience of profound anguish that had become a public health crisis. Since then it has reached new heights. Loneliness assumes many forms, from enduring physical isolation to feeling rejected because of difference, and it can have devastating consequences for our physical and mental health. As the founder of Project UnLonely, Jeremy Nobel unpacks our personal and national experience of loneliness to discover its roots and take steps to find comfort and connection. Dr. Nobel leverages many voices, from pioneering researchers, to leaders in business, education, the arts, and health care, to the lived experience of lonely people of every age, background, and circumstance. He discovers that the pandemic isolated us in ways that were not only physical, and that, at its core, a true sense of loneliness results from a disconnection to the self. He clarifies how meaningful reconnection can be nourished and sustained. And he reveals that an important component of the healing process is engaging in creativity. Make things! Supportive, clear-eyed, and comforting, this is the book we will take into our new normal and rely on for years to come"--